Accounting Conservatism, Intellectual Capital, Capital Structure in The Financial Performance of Consumer Good Companies - Heni Pujiastuti (Jurnal Aplikasi Bisnis dan Manajemen, 2024)
Background: The importance of intellectual capital for stakeholders in making investment decisions, along with the role of accounting conservatism for management, investment becomesa decision that is well-considered and measurable. Thus, through this research, investors are expected to be able to make their investment decisions well in the future.Purpose: This study aims to determine the relationship between accounting conservatism, intellectual capital, and capital structure in achieving financial performance. Design/methodology/approach: This study uses a quantitative method with a linear regression model and panel data. A total of 190 data have been obtained for five years based on certain characteristics. Through the Chow, Hausman, and Lagrange tests, the results are obtained in the form of a random effect, which will be used in the next test.Findings/Result: The results reveal that accounting conservatism has a significant influence on achieving financial performance, as well as intellectual capital and capital structure also have a significant influence on financial performance. Conclusion: There is a significant positive relationship between intellectual capital and firm value in the consumer goods sector listed on the Indonesia Stock Exchange. This indicates that intellectual capital plays an important role in creating value for the company and its stakeholders. In addition, accounting conservatism was found to be important in monitoring the company's investment decision-making. The findings of this study can provide insights for stakeholders on how the examined variables influence firm financial performance and aid in making investment decisions in the consumer goods sector in Indonesia, especially during the COVID-19 pandemic.Originality/value (State of the art): To explore the relationship between intellectual capital, accounting conservatism, and their impact on financial performance in the Indonesian consumer goods sector. Additionally, the research examines other factors, such as technological innovation, social responsibility, and supply chain management, and their influence on financial performance. The study also delves into factors that contribute to economic prosperity in emerging market economies, particularly in Indonesia, which may aid investors and policymakers in making well-informed decisions. The research employs advanced methodologies, including panel data regression analysis with robust standard errors, and builds on existing literature in financial performance and intellectual capital in emerging market economies. Ultimately, this research contributes to the advancement of the field and provides a foundation for future research. Keywords: accounting conservatism, intelectual capital, capital structure, financial performance